Informatics in Primary and Secondary Schools: Revisions in Macedonian Education - Jovanov, Mile; Mihova, Marija; Stankov, Emil; Ackovska, Nevena (FCSE, 2012)
Informatics is important subject in the Macedonian educational curriculum. During last 15 years, dramatic changes of the curriculum (in positive and negative directions) have happened, making the process interesting for observation. In this paper we present the state of the curriculum in Macedonian primary and secondary schools, concerning informatics, the most recent changes and plans for near future.